2010
DOI: 10.1136/qshc.2009.032235
|View full text |Cite
|
Sign up to set email alerts
|

How different are complications that affect the older adult inpatient?

Abstract: For inpatients aged >70 years, the risks of complications increase. The incidence of hospital-acquired diagnoses in older adults differs significantly from incidence rates found in younger cohorts. Urinary tract infection and alteration to mental state are more common in older adult inpatients. Surprisingly, these complexities do not result in additional costs when compared with costs for the same complications in younger adults. Greater awareness of these differing patterns will allow patient safety efforts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The increased LOS of 3.6 days attributable to the four key complications is similar to other research, ranging from 1 to 9 days [ 22 ]. Complications are more common in older adult inpatients and, though no more costly, they occur more often [ 4 ]. Similarly, we found that, once a complication occurs, the cost is similar for people with and without dementia but they occur more often among dementia patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased LOS of 3.6 days attributable to the four key complications is similar to other research, ranging from 1 to 9 days [ 22 ]. Complications are more common in older adult inpatients and, though no more costly, they occur more often [ 4 ]. Similarly, we found that, once a complication occurs, the cost is similar for people with and without dementia but they occur more often among dementia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Study limitations include a reliance on hospital discharge data, though we are fortunate that Australia’s hospital data reliability and quality is highly regarded since the worldwide initiation of data dictionaries in the early 1990s (see [ 28 ]), and the study is strengthened by a comprehensive approach to data linkage modelled by the Australian Institute of Health and Welfare. Other limitations are the lack of ‘condition-onset flags’ [ 4 ] to improve accuracy in identifying hospital-acquired complications. However, our patient-level risk-adjustment approach is the most refined method currently published with this level of costing detail for the aged population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar complications average almost four times the LOS of separations than those without complications [ 15 ]. These common but relatively inexpensive (per case) complications, such as urinary tract infections and pneumonias, tend to cost the most to health systems because they are so common [ 34 ]. The combined cost of just four common hospital-acquired complications (urinary tract infections, pressure injuries, pneumonia and delirium) was found to be associated with 25% of the above-average length of stay in one Australian state among older adults, with eightfold increase in LOS, and double the estimated mean episode cost [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we determined baseline kidney function before hospitalization using outpatient laboratory data to define both eGFR and proteinuria. Prior studies have focused largely on specific populations of hospitalized patients, such as those defined by age, diagnostic category (cardiac surgery, intensive care unit, and post-myocardial infarction) or treatment by a specific health care provider or institution, thereby limiting their generalizability (17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%